2009
DOI: 10.1016/j.jvs.2009.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of clinically significant postprocedural hypotension after carotid endarterectomy and carotid angioplasty with stenting

Abstract: Postprocedural hypotension occurs more commonly with CAS than CEA and is associated with increased postprocedural myocardial infarction and length of stay, and death. Nitrates and tobacco use predict a higher incidence of postprocedural hypotension. High-risk patients should be aggressively managed to prevent the increased morbidity and mortality due to postprocedural hypotension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 28 publications
1
35
1
Order By: Relevance
“…[21][22][23] In the current study, 12% of the patients treated by CAS had periprocedural hemodynamic depression requiring treatment, whereas uncontrolled series of patients treated by CAS have reported frequencies of arterial hypotension or hemodynamic depression ranging from 19% to 51%. 17,19,[24][25][26] This difference may be explained by ascertainment bias because the assessment of hemodynamic depression was a primary aim of some of the observational studies but not of ICSS. In addition, definitions for hypotension or hemodynamic depression as a composite measure differed between ICSS and the observational studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23] In the current study, 12% of the patients treated by CAS had periprocedural hemodynamic depression requiring treatment, whereas uncontrolled series of patients treated by CAS have reported frequencies of arterial hypotension or hemodynamic depression ranging from 19% to 51%. 17,19,[24][25][26] This difference may be explained by ascertainment bias because the assessment of hemodynamic depression was a primary aim of some of the observational studies but not of ICSS. In addition, definitions for hypotension or hemodynamic depression as a composite measure differed between ICSS and the observational studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore possible that these could have occurred at any time between the start of the revascularization and discharge. However, based on observations in uncontrolled series, 17,19,[24][25][26] we expect that the majority of hemodynamic events would have occurred during or immediately after CAS or CEA. For this reason, most if not all MRI scans will have been performed after the development of hemodynamic depression.…”
Section: January 2014mentioning
confidence: 99%
“…34 With detailed multimodal preoperative assessment and careful determination of angioplasty balloon size, the incidence of prolonged hypotension could be suppressed 10% (8/80) in our study, compared with other studies. 12,13,15,35,36 Once prolonged CSR occurred, continuous intravenous vasopressor infusion was immediately administered with monitoring of vital signs, urine output, and neurologic signs and symptoms. Despite the prevention of excessive hypotension and the maintenance of sufficient urine output, prolonged CSR was an independent risk factor for CIN.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,14 -16 Controlled but nonrandomized studies have suggested that arterial hypotension is a more frequent complication after CAS than after CEA. 17,18 In the randomized Endarterectomy Versus Angioplasty in Patients With Symptomatic Severe Baseline measurement is at randomization. Negative within-group scores mean a decrease from baseline.…”
Section: Discussionmentioning
confidence: 99%